A Combined Model of Human iPSC‐Derived Liver Organoids and Hepatocytes Reveals Ferroptosis in DGUOK Mutant mtDNA Depletion Syndrome. Issue 10 (8th March 2021) - Guo, Jingyi; Duan, Lifan; He, Xueying; Li, Shengbiao; Wu, Yi; Xiang, Ge; Bao, Feixiang; Yang, Liang; Shi, Hongyan; Gao, Mi; Zheng, Lingjun; Hu, Huili; et al.
Abstract: Mitochondrial DNA depletion syndrome (MDS) is a group of severe inherited disorders caused by mutations in genes, such as deoxyribonucleoside kinase (DGUOK). A great majority of DGUOK mutant MDS patients develop iron overload progressing to severe liver failure. However, the pathological mechanisms connecting iron overload and hepatic damage remains uncovered. Here, two patients' skin fibroblasts are reprogrammed to induced pluripotent stem cells (iPSCs) and then corrected by CRISPR/Cas9. Patient‐specific iPSCs and corrected iPSCs‐derived high purity hepatocyte organoids (iHep‐Orgs) and hepatocyte‐like cells (iHep) are generated as cellular models for studying hepatic pathology. DGUOK mutant iHep and iHep‐Orgs, but not control and corrected one, are more sensitive to iron overload‐induced ferroptosis, which can be rescued by N‐Acetylcysteine (NAC). Mechanically, this ferroptosis is a process mediated by nuclear receptor co‐activator 4 (NCOA4)‐dependent degradation of ferritin in lysosome and cellular labile iron release. This study reveals the underlying pathological mechanisms and the viable therapeutic strategies of this syndrome, and is the first pure iHep‐Orgs model in hereditary liver diseases. Abstract : Iron overload is an important feature in deoxyribonucleoside kinase mutant mitochondrial DNA depletion syndrome. A combined model of patient‐specific induced pluripotent stem cells‐derived liver organoids and hepatocytes reveals a sensitivity to iron overload‐induced ferroptosis in patients. This ferroptosis is a process by NCOA4‐dependent degradation of ferritin in lysosome and cellular labile iron release.